Spicule movement on RBCs during echinocyte formation and possible segregation in the RBC membrane - Melzak, Kathryn; Moreno Flores, Susana; Bieback, Karen (Biochimica et biophysica acta. Biomembranes, 2020)
We use phase contrast microscopy of red blood cells to observe the transition between the initial discocyte shape and a spiculated echinocyte form. During the early stages of this change, spicules can move across the surface of the cell; individual spicules can also split apart into pairs. One possible explanation of this behaviour is that the membrane forms large scale domains in association with the spicules. The spicules are formed initially at the rim of the cell and then move at speeds of up to 3 μm/min towards the centre of the disc. Spicule formation that was reversed and then allowed to proceed a second time resulted in spicules at reproducible places, a shape memory effect that implies that the cytoskeleton contributes towards stopping the spicule movement. The splitting of the spicules produces a well-defined shape change with an increase in membrane curvature associated with formation of the daughter pair of spicules; the total boundary length around the spicules also increases. Following the model in which the spicules are associated with lipid domains, these observations suggest an experimental procedure that could potentially be applied to the calculation of the line tension of lipid domains in living cells.
Gesehen am 11.08.2025